2014
DOI: 10.1007/s10340-014-0604-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological significance of rice (Oryza sativa) planting density and nitrogen rates in managing the growth and competitive ability of itchgrass (Rottboellia cochinchinensis) in direct-seeded rice systems

Abstract: Ecological significance of rice (Oryza sativa) planting density and nitrogen rates in managing the growth and competitive ability of itchgrass (Rottboellia cochinchinensis) in direct-seeded rice systems Abstract Current understanding is that high planting density has the potential to suppress weeds and crop-weed interactions can be exploited by adjusting fertilizer rates. We hypothesized that (a) high planting density can be used to suppress Rottboellia cochinchinensis growth and (b) rice competitiveness again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The largest investment in shoots by L. hexandra at high densities of the invasive probably occurs because Poaceae are, in general, highly sensitive to shading conditions. Allocation to shoot biomass, relative to root biomass, is likely to be a response to light limitation under high competition, as observed for other herbaceous species ( Gibson et al, 2004 ; Awan et al, 2015 ). On the other hand, increased allocation to roots in P. cordata indicates a response to root competition (for other examples, see Bakker and Wilson, 2001 ; Schiffers et al, 2011 ; Zhu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 80%
“…The largest investment in shoots by L. hexandra at high densities of the invasive probably occurs because Poaceae are, in general, highly sensitive to shading conditions. Allocation to shoot biomass, relative to root biomass, is likely to be a response to light limitation under high competition, as observed for other herbaceous species ( Gibson et al, 2004 ; Awan et al, 2015 ). On the other hand, increased allocation to roots in P. cordata indicates a response to root competition (for other examples, see Bakker and Wilson, 2001 ; Schiffers et al, 2011 ; Zhu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 80%
“…Our study showed that seedling emergence had significant positive correlation with SVI (r = 0.96, P < 0.001), LAI (r = 0.90, P < 0.001), plant biomass (Pearson correlation, r = 0.59, P < 0.001). Previously researchers also reported that, seedling emergence correlated positively with SVI 16,47 , leaf area index (LAI) 47,48 and plant biomass production 15 . This has also been observed in other crops, including sorghum (Sorghum bicolor) 49 and sunflower (Helianthus annuus) 23 .…”
Section: Discussionmentioning
confidence: 89%
“…Growth parameters (seedling root and shoot length) were measured at 6, 10, 15, and 21 days after sowing (DAS) on 12 seedlings 48,66 . Seedling emergence percentage was calculated at 21 days after sowing based on the number of seedlings that emerged above the surface of floodwater following the below formula 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Butachlor fb orthosulfamuron fb butachlor + propanil also provided similar number of panicles m -2 and pyrazosulfuron-ethyl fb orthosulfamuron fb 2,4-D amine gave similar number of filled grains panicle -1 with weed-free control. This might be happened for ensuring better weed control by those treatment that leads to reduced crop-weed competition and facilitated the uptake of more nutrients resulted healthier rice plants with more tillers and panicles (Ahmed and Chauhan, 2014;Awan et al, 2014). 'fb' = 'followed by', 'aceto + bensul' = 'acetochlor + bensulfuron methyl', 'orthosul' = 'orthosulfamuron', 'buta + prop' = 'butachlor + propanil', '2,4-D' = '2,4-D amine', 'CV' = co-efficient of variance…”
Section: Number Of Panicles M -2 and Filled Grains Panicle -1mentioning
confidence: 99%